ORIBÁTIDOS DE CHILE (ACARIÑA: ORIBATIDA) II. ESPECIES ASOCIADAS A PLANTAS ACUÁTICAS (Acta Entomológica Chilena, 2022)
The Oribatid mite’s species living on aquatic or wet plants were studied. Fifteen localities were sampled,from the II to the X Regions of Chile, that is, from the northern desertic ecosystems, to the Southerntemperature región.A surprisingly poor number of species was found, they were mostly omnipresent despite the extendedsampled zones. While different species with a high diversity inhabit the terrestrial ecosystems (desert, calidsteppes, bushes, sclerophilous forest, temperature forest, coid altitudinal steppes), the species found alongthe different water systems studied were a monotonous group, all present in slow water currents and only onthe vegetation near the borders.Ten species of Oribatida were found. One is found only in properly aquatic plants; three others were foundeither on aquatic plants or in wet mosses standing on soils or rocks touching the water; others six were foundonly in wet plants or mosses. The geographic distribution is given for each species.The densities of the four hydrophilous species show an extreme agregation, with few samples showingvery high densities and many samples showing very low ones, being the common case to found 0, 1 or 2individuáis by sample. Average densities, their standard deviations, the mode and the sample frequency aregiven for each species.Hydrozetes lemnae was reared in the laboratory and they didn’t show the phenomenon of “aquaticlevitation”; they remain in decomposing plants, eating them and reproducing there parthenogenetically; onlyfemales were then found.
Keywords: Mites, Oribatida, hydrophylous, Chile